Welcome to the Green Village - A.J.M. van Wijk (IOS Press, 2013)
A sustainable world can only be achieved by an open collaboration between science, business and the public. That is why we create the Green Village: an innovative, lively, interactive & challenging environment where entrepreneurs, innovators, companies, artists, teachers and visitors can meet, work and play to develop, apply and experience innovative sustainable products and solutions. In the Green Village you will find Future Labs for paradigm-shifting system research, resulting in icon projects such as the Car Park Power Plant, the Harp and the Energy Wall. The Green Village will be sustainably powered by the Engines, with 'heart', 'veins' and 'lungs' that supply energy and water, treat waste water and solid waste into useful new products and provide energy and transport fuels like electricity and hydrogen. It will also house the Greentech Store, an innovative co-making shop for 3D printing, apps, crowd funding & more. And it will be the stage for many sustainability Events: exhibitions, shows, contests, workshops, games, challenges, conferences, etcetera.The Green Village is located at Delft Campus, enabled by Delft University of Technology and empowered by a lively online community of scientists, entrepreneurs and you! Its vision: "Creating a sustainable, lively and entrepreneurial environment where we discover, learn and show how to solve society's urgent challenges".